Construction of Large Non‐Localized π‐Electron System for Enhanced Sodium‐Ion Storage. Issue 8 (9th December 2021) - Wang, Liang‐Yu; Ma, Chao; Hou, Cheng‐Cheng; Wei, Xiao; Wang, Kai‐Xue; Chen, Jie‐Sheng
Abstract: Organic electrode materials with the advantages of renewability, environment‐friendliness, low cost, and high capacity have received widespread attention in recent years for sodium‐ion batteries. However, small molecular organic materials suffer from issues such as low conductivity and the high dissolution rate in electrolytes. Herein, a phthalocyanine derivative (TPcDS) with a large non‐localized π‐electron system, obtained through thermodynamic polymerization of 4‐aminophthalonitrile (AP) monomers, is designed to address these issues. According to the density function theory calculation, six sodium ions can be attracted by one polymer molecule, indicating a high theoretical capacity of 375 mA h g ‐1 . The TPcDS molecule realizes sodium storage through a non‐localized π‐electron system of phthalocyanine macrocycles. When employed as an anode material for sodium‐ion batteries, the functional groups of phthalocyanine macrocycles, such as CN groups in TPcDS, experience obviously reversible structural variation upon discharge/charge. A high reversible capacity of 364 mAh g ‐1 is achieved at a current density of 0.05 A g ‐1, and a charge capacity of as high as 246 mAh g ‐1 is still maintained after 500 cycles at 0.1 A g ‐1 . This work provides an effective strategy for the design and synthesis of new oligomeric organic electrode materials. Abstract : A strategy based on the formation of a large non‐localized π‐electron system is proposed for the design of high‐performance organic electrode materials. Benefitting from the big π‐electron conjugated system, the triaminephthalocyanine derivative prepared by the catalytic reaction of three 4‐aminophthalonitrile molecules exhibits large reversible capacity and significantly improved cycling and structural stability.